The Effect of E-Service Quality on E-Customer Satisfaction and E-Customer Loyalty in ShopeeFood Services in DKI Jakarta - Shaomi Fujiyanti Amalia; Arif Kuswanto (Jurnal Ad'ministrare, 2023)
ShopeeFood is an online food delivery service feature that provides online food and beverage buying and selling transactions. With the online food delivery feature, it might facilitate that people to buy food quickly and easily without having to travel far. This certainly affects how much e-service quality is provided by ShopeeFood for e-customer satisfaction and e-customer loyalty by using OFD (online food delivery) at ShopeeFood. This study is a quantitative and descriptive research with nonprobability using purposive sampling. Data processing on these findings was carried out using the SPSS version 27 software application. It was found that the level of e-customer satisfaction can be positively and significantly influenced by e-service quality. In addition, e-service quality can also have a positive and significant effect on e-customer loyalty in ShopeeFood services.